The interplay between gut microbiota and the brain-gut axis in Parkinson’s disease treatment - Jia, Xi; Wang, Qin; Liu, Meilingzi; Ding, Jia-yuan (Frontiers in Neurology, 2024)
This study delves into the pivotal role of the gut microbiota and the brain-gut axis in Parkinson’s Disease (PD), a neurodegenerative disorder with significant motor and non-motor implications. It posits that disruptions in gut microbiota—dysbiosis—and alterations in the brain-gut axis contribute to PD’s pathogenesis. Our findings highlight the potential of the gastrointestinal system’s early involvement in PD, suggested by the precedence of gastrointestinal symptoms before motor symptoms emerge. This observation implies a possible gut-originated disease pathway. The analysis demonstrates that dysbiosis in PD patients leads to increased intestinal permeability and systemic inflammation, which in turn exacerbates neuroinflammation and neurodegeneration. Such insights into the interaction between gut microbiota and the brain-gut axis not only elucidate PD’s underlying mechanisms but also pave the way for novel therapeutic interventions. We propose targeted treatment strategies, including dietary modifications and fecal microbiota transplantation, aimed at modulating the gut microbiota. These approaches hold promise for augmenting current PD treatment modalities by alleviating both motor and non-motor symptoms, thereby potentially improving patient quality of life. This research underscores the significance of the gut microbiota in the progression and treatment of PD, advocating for an integrated, multidisciplinary approach to develop personalized, efficacious management strategies for PD patients, combining insights from neurology, microbiology, and nutritional science.